2019
DOI: 10.1111/rssb.12349
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Sampling from Massive Block Model Graphs with Personalized PageRank

Abstract: Summary The paper provides statistical theory and intuition for personalized PageRank (called ‘PPR’): a popular technique that samples a small community from a massive network. We study a setting where the entire network is expensive to obtain thoroughly or to maintain, but we can start from a seed node of interest and ‘crawl’ the network to find other nodes through their connections. By crawling the graph in a designed way, the PPR vector can be approximated without querying the entire massive graph, making i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…Here t is a chosen threshold constant. We extend the setting of a single seed node in [14] and [16] to multiple seed nodes, but still make the assumption that they all belong to the same community. While it is unlikely that all papers cited by a specific topic come from the same community, the threshold t helps us prune the vector π and make the assumption more reasonable.…”
Section: Preliminaries and The Dc-sbmmentioning
confidence: 99%
See 4 more Smart Citations
“…Here t is a chosen threshold constant. We extend the setting of a single seed node in [14] and [16] to multiple seed nodes, but still make the assumption that they all belong to the same community. While it is unlikely that all papers cited by a specific topic come from the same community, the threshold t helps us prune the vector π and make the assumption more reasonable.…”
Section: Preliminaries and The Dc-sbmmentioning
confidence: 99%
“…where p i is the ith entry in the PPR vector. [16] showed that under the DC-SBM, adjusting by the degrees leads to a consistent ordering of the entries in p * so that entries with the highest values belong to the target community. Formally, let n be a community size cutoff.…”
Section: Preliminaries and The Dc-sbmmentioning
confidence: 99%
See 3 more Smart Citations